Crosswalk of participation self-report measures for aphasia to the ICF: what content is being measured?. (June 2015) - Brandenburg, Caitlin; Worrall, Linda; Rodriguez, Amy; Bagraith, Karl
Abstract Purpose: Community participation is of importance to people with aphasia, who are at risk of becoming socially isolated. This study investigates the content of measures of community and social participation for this population by crosswalking items to the ICF. This will evaluate: (1) to what extent the included assessments assessed participation only, (2) what content appeared most frequently and (3) which response formats were utilised. Methods: Instruments were identified from four systematic reviews and a literature search. 111 instruments that were self-reported, developed for adults and published in English were identified. Items were linked to ICF domains, and third-level categories of the Activities and Participation chapter. Results: Ninety instruments (2426 items) were included. Of these, 29 instruments contained over 50% participation items. The most frequently included participation categories in this subset were education, paid employment, recreation, socialising, being a carer, relating with friends, family and spouses, volunteer work, managing finances, community life, civic duties, human rights and religion/spirituality. Self-care, mobility and domestic life concepts were also frequently reported. Commonly used response formats were restriction, frequency and satisfaction. Conclusions: Few instruments solely assessed participation according to our operationalisation. This study provides a list of possible measures for use in assessing participation. Implications for Rehabilitation Participation restriction, as defined by the International Classification of Functioning, Disability and Health, is a key concern for people with aphasia. By conducting the crosswalk, we have identified that self-report measures of participation vary widely in content and response metrics, and often include activity, body function, environmental and quality of life items. This review may assist rehabilitation researchers and clinicians in choosing a measure of participation restriction for people with aphasia and other populations by listing instruments with over 50% participation content. These results also indicate that the construct of participation needs to be adequately and uniformly defined so that the ICF to be used effectively as a framework for health status measurement.